Industry-science connections in agriculture: Do public science collaborations and knowledge flows contribute to firm-level agricultural research productivity? - Andrew A. Toole; John L. King (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
Prior research shows long-run productivity growth in agriculture is associated with increases in the stock of public scientific knowledge and private patented inventions. However, private inventions may be a function of the stock of public knowledge. In this paper, we examine the possibility that public knowledge contributes to productivity through its relationship with private sector invention. Our analysis identifies connections between the stock of public knowledge and private firm R&D and examines whether the degree of 'connectedness' to public science is associated with greater firm-level research productivity in agriculture. Bibliographic information identifies the nature and degree to which firms use public agricultural science through citations and collaborations on scientific papers. Fixed effects models show that greater citations and collaborations with university researchers are associated with greater private agricultural research productivity.
Keywords: Q16; O31; 330; Public science; research productivity; patents; citations; collaboration; R&D; bibliometrics